2009
DOI: 10.1590/s0100-40422009000800006
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity against postharvest fungi by extracts from Colombian propolis

Abstract: Recebido em 10/7/08; aceito em 24/4/09; publicado na web 22/9/09 ANTIFUNGAL ACTIVITY AGAINST POSTHARVEST FUNGI BY EXTRACTS FROM COLOMBIAN PROPOLIS. The aims of the present study were to evaluate the antifungal properties of Colombian propolis extracts against Colletotrichum gloeosporioides and Botryodiplodia theobromae, and to isolate and identify the main constituents from the active extracts. Therefore, propolis samples were thoroughly extracted with n-hexane/methanol (EPEM), dichloromethane, ethyl acetate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 15 publications
2
32
0
2
Order By: Relevance
“…Mello et al (2006) suggested that the antifungal activity of propolis maybe due to the changes in the cell wall that leading to increasing of volume and membrane rupture. Previous study found three compound isocupressic acid, (+)-agathadiol and epi-13-torulosol that have antifungal activity against the tested fungi on culture medium by reduce radial mycelium grow (Meneses et al, 2009). Ozcan et al (2003) also reported that the methanolic propolis extract had large scale effect to inhibition mycelial growth against many phytopathogenic fungi in culture medium.…”
Section: Discussionmentioning
confidence: 93%
“…Mello et al (2006) suggested that the antifungal activity of propolis maybe due to the changes in the cell wall that leading to increasing of volume and membrane rupture. Previous study found three compound isocupressic acid, (+)-agathadiol and epi-13-torulosol that have antifungal activity against the tested fungi on culture medium by reduce radial mycelium grow (Meneses et al, 2009). Ozcan et al (2003) also reported that the methanolic propolis extract had large scale effect to inhibition mycelial growth against many phytopathogenic fungi in culture medium.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, independent of whether the protective chemical variability is maintained, the inhibitory activity of propolis is associated with the synergy of its components, consistent with Garedew et al (2004), Meneses et al (2009) and Petrova et al (2010), and it has not been shown experimentally that only a single component has greater activity than the total extract (Agüero et al, 2010). However, Treutter (2006) discussed the significance of flavonoids in the protection and resistance of plants to phytopathogens, particularly fungi, and phenolics and flavonoids are proposed to be the main antimicrobial components of propolis.…”
Section: Discussionmentioning
confidence: 58%
“…The control of phytopathogenic fungi by propolis has been proposed by Hegazi and Abd El Hady (2002) who evaluated the use of Egyptian propolis to control nine postharvest fungi and reported successful inhibition of the fungi, with minimum inhibitory concentration values ranging between 1.2-3.6 mg mL . In other countries, samples of the local propolis have been evaluated by Őzcan et al (2004), Quiroga et al (2006), Giovanelli (2008), Meneses et al (2009), andÖzdemir et al (2010) who obtained interesting results against phytopathogenic fungi. However, the development of a propolis extract for use as an agricultural fungicide has not been given much attention (Hegazy and Abd El Hady, 2002;Quiroga et al, 2006) in Chile, and data regarding its action against important economical agricultural fungi are limited.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the terpenoid torulosol was among the major compounds that differentiated hybrids and P. taeda in both standing and felled trees: torulosol and its derivatives have been identified in extracts that show antifungal activity (Meneses et al, 2009). The majority of compounds we detected in our samples were non-volatile oleoresins, composed mostly of monoterpenes and diterpene resin acids, which can present both a physical and chemical defence system against invading pathogens and insects.…”
Section: Discussionmentioning
confidence: 71%